2020
DOI: 10.3389/fchem.2020.00406
|View full text |Cite
|
Sign up to set email alerts
|

Insightful Backbone Modifications Preventing Proteolytic Degradation of Neurotensin Analogs Improve NTS1-Induced Protective Hypothermia

Abstract: Therapeutic hypothermia represents a brain-protective strategy for multiple emergency situations, such as stroke or traumatic injury. Neurotensin (NT), which exerts its effects through activation of two G protein-coupled receptors, namely NTS1 and NTS2, induces a strong and long-lasting decrease in core body temperature after its central administration. Growing evidence demonstrates that NTS1 is the receptor subtype mediating the hypothermic action of NT. As such, potent NTS1 agonists designed on the basis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…Our results showed that NT(8-13) and JMV449 had no effect on body temperature, compared to saline-treated animals while JMV5170 and JMV5206 induced a strong and sustained decrease of body temperature of more than 2°C for up to 1 hour. These results are consistent with previous findings showing that the stability of NT(8-13) analogs is a key factor driving hypothermic response and that the increased stability can even compensate for a reduction in binding affinity at NTS1 [39,71]. Indeed, NT(8-13) and JMV449, which exhibit a plasma half-life of less than 10 min did not induce hypothermia.…”
Section: Jmv5296 Elicits Moderated Hypotensive Response and No Hypothermiasupporting
confidence: 93%
See 3 more Smart Citations
“…Our results showed that NT(8-13) and JMV449 had no effect on body temperature, compared to saline-treated animals while JMV5170 and JMV5206 induced a strong and sustained decrease of body temperature of more than 2°C for up to 1 hour. These results are consistent with previous findings showing that the stability of NT(8-13) analogs is a key factor driving hypothermic response and that the increased stability can even compensate for a reduction in binding affinity at NTS1 [39,71]. Indeed, NT(8-13) and JMV449, which exhibit a plasma half-life of less than 10 min did not induce hypothermia.…”
Section: Jmv5296 Elicits Moderated Hypotensive Response and No Hypothermiasupporting
confidence: 93%
“…Bold indicates synthetic changes from native peptide NT (8)(9)(10)(11)(12)(13). Data are expressed as mean ± SEM [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all the possible approaches, the introduction of unnatural amino acids and peptide backbone modifications has led to ligands with improved selectivity toward the target [36][37][38][39][40]. While the incorporation of an unnatural amino acid could be limited to a substitution, an extensive variety of backbone modifications could be inserted [41,42].…”
Section: Introductionmentioning
confidence: 99%